Efektifitas bahan ajar elektronika digital berbasis multimedia di Jurusan Pendidikan Teknik Elektronika Universitas Negeri Makassar - Mahmud Mustapa; Ummiati Rahmah (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to determine the effectiveness of the use of multimedia-based digital electronics teaching materials in the electronics engineering department of Makassar State University. This type of research is a type of research experiment. Data is collected by the method of observation, testing and documentation. Techniques for analyzing data qualitatively and quantitatively. The results of the study found that the value of learning outcomes for students using multimedia learning was higher than conventional classes. This is also proven by the results of statistical tests with the results found, namely there are differences in student learning outcomes between the experimental class and conventional classes for the theory of digital electronics.